Pengaruh Return On Assets Dan Leverage Terhadap Penghindaran Pajak pada Perusahaan Manufaktur yang Terdaftar di BEI - N Heriyah (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2020)
Tax avoidance is mostly done by taxpayers because this is legal as long as the tax avoidance is carried out not in violation of tax laws and regulations in force in Indonesia. There are several factors that affect tax avoidance including Return on assets and leverage. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2017 observation period. The method of determining the sample used is the purposive sampling method with a sample of 159. Based on the results of multiple linear regression analysis, the results obtained that the variable Return On Assets and leverage positive effect on tax avoidance by manufacturing companies listed on the Indonesia Stock Exchange.